Direct hydrothermal synthesis of highly ordered Sn-SBA-15 mesoporous materials - Shah, Pallavi; Ramaswamy, Arumugamangalam V.; Ramaswamy, Veda (Chemistry Letters, 2006)
Well-ordered Sn4+-incorporated mesoporous silica SBA-15 samples have been synthesized from tetraethyl orthosilicate (TEOS) and SnCl4 (Si/Sn = 114-15) using nonionic surfactants under a slightly higher pH medium (optimum H2O to HCl molar ratio) and characterized by XRD (an increase in lattice parameter), TEM (no SnO2 species) and UV-vis spectral (absorption at 211 nm) techniques to show that Sn4+ ions are in tetrahedral coordination in Sn-SBA-15.

Direct hydrothermal synthesis of mesoporous Sn-SBA-15 materials under weak acidic conditions - Shah, P.; Ramaswamy, A. V.; Lazar, Karoly; Ramaswamy, Veda (Microporous and Mesoporous Materials, 2007)
A direct synthetic route for the preparation of Sn-SBA-15 materials with n(Si)/n(Sn), ratios ranging from 100 to 10 under milder acidic conditions than normally employed for the preparation of Si-SBA-15 is reported. The changes in the pH conditions of the gel were made through an adjustment of the molar ratio of n(H2O) to n(HCl) (< 1 pH < 2) during preparation. The samples prepared under three different acidic conditions have been characterized by various techniques. An expansion of the lattice (powder XRD) and an increase in mesopore area (low temperature N-2 adsorption) indicate that the hexagonal structure of the SBA- 15 is maintained with no loss of long range ordering. The UV-vis reflectance spectra of Sn-SBA-15 samples show the presence of Sn4+ ions both in tetrahedral and octahedral environment. Si-29 MAS NMR spectra of samples prepared under an intermediate acid condition show the presence Of Q(3) and Q(4) species. Their ratio increases with a decrease in tin content. The presence of Si in (2Si, 2Sn) i.e., Q(2) environment may point to incorporation of considerable Sn4+ ions in tetrahedral positions. Sn-Mossbauer spectroscopic studies reveal that Sn2+ species form upon reductive treatments and can probably be stabilized in the pore wall upon reoxidation. This to some extent is an indication of the formation and stabilization of Si-O-Sn-O-Si linkages in Sn-SBA-15. A progressive increase in the pH of the medium (increasing the n(H2O) to n(HCl), ratio) results in the location of Sn4+ ions, (a) at the surface of the mesopores (surface of the corona region) as a thin film of SnO2 or small aggregates (loss in mesopore area) depending on the concentration of Sn; (b) at the walls of the mesopore structure, substituting Si4+ ions (some lattice expansion and tetrahedral Sn4+ ions); and/or (c) as a part of the corona region, neutralizing the resulting Si-OH groups (a loss of micropore area and octahedral Sn4+ ions). The studies reveal that the method of preparation, n(H2O)/n(HCl) ratio and the n(Si)/n(Sn) ratio (concentration of SnCl4) of the gel significantly influence the type of tin species in the resulting Sn-SBA-15 samples. (c) 2006 Elsevier Inc. All rights reserved.
Keywords: direct synthesis of Sn-SBA-15; Si-29 and Sn-119 MAS-NMR; Sn-mossbauer spectroscopic studies; Sn-SBA-15; tin-mesoporous silica

Direct synthesis of well-ordered mesoporous Al-SBA-15 and its correlation with the catalytic activity - Bhange, Pallavi; Bhange, Deu S.; Pradhan, Sivaram; Ramaswamy, Veda (Applied Catalysis A-General, 2011)
The synthesis of Al-SBA-15 under milder acidic conditions were made through an adjusting the molar H(2)O/HCl ratio which indicate the formation of Si-O-Al linkages that lead to isomorphous substitution of Si(4+) by some Al(3+) ions. By adjusting the H(2)O/HCl molar ratio, Al gets incorporated into the lattice of SBA-15, which is evidenced by XRD. N(2) adsorption, TEM, (29)Si and (27)Al MAS NMR spectroscopic data. Aluminium incorporated SBA-15 samples retained both structural and textural properties of SBA-15. The (27)Al MAS NMR confirms that a large proportion of the Al is inserted into tetrahedral positions within the framework. The Al(3+) ions could assume a tetrahedral coordination and be part of the hexagonal structure of silica in Al-SBA-15. In the present study, we have examined the effectiveness of Al-SBA-15, as an acid catalyst for the esterification of acetic acid and in benzylation of anisole. The high activity of Al-20 sample in esterification reaction has been attributed to isolated, generally tetrahedrally coordinated, framework Al species. While in benzylation of anisole, the best result was achieved with Al-5 catalyst. The selectivity for benzylanisole increases and that for dibenzylether decreases with increase in the Si/Al ratio of Al-SBA-15. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Al-SBA-15; Benzylation of anisole; Esterification of acetic acid